A report on the fauna of the estuaries of the River Tamar and the River Lynher. - Percival, E. (Journal of the Marine Biological Association of the United Kingdom, New Series, 1929)
M1301
Kristian Fauchald's Polychaeta DB Ant'Phipoda Literature database fig. 1, chart 1. (v.1929).; NeMys doc_id: 2381